Pengaruh Pemasaran Media Sosial dan Gaya Hidup yang Dimoderasi oleh Pendapatan terhadap Keputusan Pembelian pada Konsumen Coffee Shout Haurgeulis - Mursyidah Lathifah; Aang Curatman; Dedi Muhammad Siddiq (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the effect of social media marketing and lifestyle on consumer purchasing decisions at Coffee Shout Haurgeulis, with income as a moderating variable. The research employed a quantitative method. The sample consisted of 132 respondents, determined using the Slovin formula. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results indicate that social media marketing does not have a significant effect on purchasing decisions, while lifestyle has a significant effect. Income is proven to moderate the influence of lifestyle on purchasing decisions but does not moderate the effect of social media marketing on purchasing decisions. The R-square value of 0.307 indicates that purchasing decisions are influenced by the variables in the model by 30.7%, while the remaining variance is explained by other factors outside this study.